The sleepwalkers / Paul Grossman. - Grossman, Paul. (St. Martin's Press, 2010)
A high-ranking Jewish detective in Berlin in 1932, Willi Kraus finds his murder investigation of an oddly deformed and mysterious young woman made difficult by his superiors and several disturbing events.